Change Management Strategies In The Context Of Education: A Case Study Of Private School SMK X - Khalifachri Albi; Ermalina Ermalina; Sulistyo Seti Utami; Siti Maryama; Berlianingsih Kusumawati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Education is a sector that is constantly changing. These changes can be in the form of changes in curriculum, technology, policies, and so on. Schools as educational institutions need to have effective change management strategies to adapt to changes and improve the quality of education. This research aims to analyze effective change management strategies in the context of education using a case study of a private school. This research uses qualitative research methods. The data collection techniques in this research are literature review, observation, and interviews. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation, and conclusion drawing. The results showed effective change management strategies in private education at SMK X include communication, stakeholder participation, training and mentoring, and adaptive culture. Effective change management strategies can help schools to adapt to changes and improve the quality of education.